Influence of depression on suicidal ideation in students from the Peruvian jungle - Astocondor Altamirano, Jhonny Vidal (2019)
Objective: To determine the influence of depression on suicidal ideation in students from the Peruvian jungle. Materials and methods: An analytical cross-sectional study was carried out in a university population of the Peruvian jungle. The dependent variable was "suicidal ideation" and the independent variable was "depression", both measured through the Birleson and Beck scales, respectively, which were modified for Peru. These variables were cross-checked and adjusted using other variables. Results: There is a strong association between suicidal ideation and depression (p-value < 0.01). In addition, university students with depression were more prone to have medium-high suicidal ideation (PR: 7.1, 95 % CI: 3.8- 13.2). Other behaviors that were associated with the degrees of medium-high suicidal ideation were: perceiving to have little chances of being happy in the future (RP: 0.4, 95 % CI: 0.2-0.6), not feeling to be taken into account by the family (RP: 6.5, 95 % CI: 4.2-10.0), and feeling that death could generate relief (PR: 6.8, 95 % CI: 4.6-10.2). Conclusions: An association was found between the variables "suicidal ideation" and "depression", characterized by some perceptions and behaviors which reveal serious mental-sphere problems. Such problems should be taken into account by educational entities to generate detection and assistance programs for young students.